Code-switching: How ESL learners react towards it - Nordin, Noli Maishara; Rashid Ali, Farrah Diebaa (2011)
The use of more than one code of language among the Malaysian English language instructors and ESL learners in the context of formal classroom settings is widely acknowledged (Kow, 2003; Then & Ting, 2009). Many factors may contribute to the occurrence of code-switching or in other words, there must have been certain communication purposes associated which cause the code switching to occur. This study aimed to uncover the attitudes of ESL Learners towards the functions of code-switching employed by English language instructors at tertiary level. It addressed two research questions: (1) What do ESL learners think about code switching in the English classroom? (2) When does code switching serve its best functions in the English classroom for the ESL learners? Forty five diploma students were randomly selected as the respondents for this study. A survey questionnaire which focused on the students’ attitudes, usage and opinion of code switching in the classroom was utilised in the study. It was found that most of the ESL learners have positive attitudes towards code switching. The ESL learners were also reported to believe that code switching facilitates them in understanding the target language. The findings suggest that the use of code switching is necessary when the situation requires the use of first language in the classroom.